2016
DOI: 10.1007/s13205-016-0520-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of Annona species and proximate fruit composition of selected genotypes

Abstract: Understanding the genetic variation in germplasm is of utmost importance for crop improvement. Therefore, efforts were made to analyse the molecular marker based genetic diversity of 20 Annona genotypes from five different species of family Annonaceae. During analysis, a set of 11 RAPD primers yielded a total of 152 bands with 80.01 % polymorphism and PIC for RAPD ranged from 0.86 to 0.92 with a mean of 0.89. With 93.05 % polymorphism, 12 SSR primers produced 39 amplicons. The PIC for SSRs ranged from 0.169 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
0
15
0
2
Order By: Relevance
“…The most useful aspects of this tree are Graviola leaves. It has active ingredients, bulatacin, asimisin, and squamosin, which contain acetogenins [24]. The presence of secondary metabolites like tannins, steroids, and cardiac glycoses was revealed by a chemical screening of Graviola extract [25].…”
Section: Introductionmentioning
confidence: 99%
“…The most useful aspects of this tree are Graviola leaves. It has active ingredients, bulatacin, asimisin, and squamosin, which contain acetogenins [24]. The presence of secondary metabolites like tannins, steroids, and cardiac glycoses was revealed by a chemical screening of Graviola extract [25].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers were identified and isolated about two hundred chemical compounds from graviola; the most important being alkaloids, phenols and acetogenins [18]. Also, it has acetogenins-containing compounds, namely bulatacin, asimisin, and squamosin [19]. Also, Alitonou et al [20] detected numerous phenols, flavonoids, vitamins, and carotenoids in graviola leaves.…”
Section: Introductionmentioning
confidence: 99%
“…However, information on the composition, nutritional value and medicinal uses of the A. muricata seeds is still limited. Anuragi et al, (2016) report that the graviola seed is rich in oil and can be exploited in the oil industy. Elagbar et al, (2016) identified important fatty acids in the oil of A. muricata seeds and emphasized that this oil can be exploited for industrial, cosmetic, and medicinal purposes.…”
Section: Introductionmentioning
confidence: 99%